Prevalence of work values among Universiti Pertahanan Nasional Malaysia (UPNM) cadets - Syafiqa Hazira,; Norshaffika Izzaty Zaiedy Nor,; Mohd Nasir Selamat,; Ramos, Hazel Melanie (Penerbit Universiti Kebangsaan Malaysia, 2024)
The rigorous physical demands of military training, the hierarchical structure of the military, and the level of support provided by superiors may significantly impact the psychological well-being of cadets. This research aims to examine the prevalence of work values and the differences of risk factors such as gender, age and academic background on work values among military cadets. A total of 887 trainee cadets were selected through purposive sampling to complete questionnaires adapted from Donald Super's Work Values Inventory (WVI). The results showed that UPNM cadets prioritised the following work values: economic return, surroundings, supervisory relationships, achievement, way of life, associates, altruism, creativity, prestige, and security, with economic return being the most prevalent among 491 cadets. Additionally, there was a significant difference between gender and work values, as male cadets scored higher than female cadets in areas such as creativity, management, achievement, and more. This research highlights the importance of understanding work values among military cadets, particularly the emphasis on economic return. By integrating these insights into training frameworks, military institutions can enhance work values and psychological well-being, ultimately fostering a more supportive training environment and improving on-time graduation rates.